1977
DOI: 10.1084/jem.146.3.844
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T-cell activation by polyribonucleotides: DNA synthesis is not required.

Abstract: We have shown that cytotoxic T cells can be polyclonally activated by a short exposure to complexes of polyadenylic:polyuridylic acid (poly A:U). Activation is optimal at a dose of 100 microgram/ml poly A:U and occurs during a 2 h incubation period in the absence of antigen. Killing of allogeneic, but not syngeneic, target cells can be observed after 12 h in culture and peaks after 21-24 h in the absence of any nonspecific binding ligand. The observed cytotoxicity is mediated by T lymphocytes and dose not requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In vitro expression of cytotoxicity without Con A included in the assay system was only possible when the activated cells were allogeneic to the targets [14]. A similar immunological specificity has been shown following in vitro activation using both Con A [2,9,14] and the polyclonal Tcell activator poly A:U [4]. Self-tolerance in these systems can be interpreted as a complete absence of clones capable of being activated by polyclonal T cell activators to express cytotoxicity to self-determinants, in accordance with the clonal elimination hypothesis.…”
mentioning
confidence: 96%
“…In vitro expression of cytotoxicity without Con A included in the assay system was only possible when the activated cells were allogeneic to the targets [14]. A similar immunological specificity has been shown following in vitro activation using both Con A [2,9,14] and the polyclonal Tcell activator poly A:U [4]. Self-tolerance in these systems can be interpreted as a complete absence of clones capable of being activated by polyclonal T cell activators to express cytotoxicity to self-determinants, in accordance with the clonal elimination hypothesis.…”
mentioning
confidence: 96%
“…These substances, typically polyinosinic acid complexed with polycytidylic acid (poly I:C), or polyadenylic acid complexed with polyuridylic acid (poly A:U) are capable of inducing interferon production by lymphocytes (Vengris & Mare, 1972), presumably because they simulate viral genetic material. They have also been shown to affect such lymphocyte functions as antibody secretion (Han &Johnson, 1976) and cytotoxicity (Bick & Moller, 1977). These latter activities may reflect augmentation of T-helper cell function, possibly mediated by increased lymphokine secretion.…”
Section: Synthetic Polynucleotidesmentioning
confidence: 99%
“…Non-specific polyclonal activation of cytotoxic T cells by poly A : U has been charcterized by Bick and Moller [5]. Their experiments showed that after a 2 h incubation in the presence of poly A:U, activation occurred in as short a time interval as 12-24 h. This occurred in the absence of antigen and independent of DNA synthesis.…”
Section: T Cellmentioning
confidence: 99%